Development of Extemporaneously Prepared Captopril Oral Dosage Forms - A Comprehensive Chronological Study - Ayman M. Al-Qaaneh (Journal of Global Pharma Technology, 2020)
Captopril is an Angiotensin-converting enzyme inhibitor, its effectiveness as an antihypertensive agent and in the treatment of several cardiovascular conditions in neonates and children has been proved clinically. Unfortunately, in many countries, it is available as a solid dosage form only. As this does not satisfy the needs of these patients in terms of dosage and pharmaceutical formulations, extemporaneously prepared formulations represent the only available solution for this situation. Many attempts have been made to study the different factors that may affect the stability of captopril in oral liquid formulations, aiming to design a formula with maximum stability profile. Although there is still debate about the effect of some factors on captopril stability, other factors have a clear role. Low storage temperature, acidic media (up to pH 4), use captopril powder, absence of heavy metals, increase drug concentration, sugar-free vehicle, decrease oxygen contents in the formulation, and excipients such as chelating agents and antioxidants are well known to increase captopril stability. Varies type of extemporaneously prepared dosage forms (liquid, powder, or tablet) with different formulations have been prepared and studied. Unfortunately, the stability of captopril in these preparations has been highly variable and sometimes conflicting results obtained, reflecting the sensitivity of captopril to a variety of factors that have not yet been completely identified. This review discusses these factors and extemporaneously prepared formulations in a comprehensive chronological way. Keywords: Captopril, extemporaneous preparation, Drug stability, Pharmaceutical formulation, Drug compounding.